Algorithm for the Use of Biochemical Markers of Bone Turnover in the Diagnosis, Assessment and Follow-Up of Treatment for Osteoporosis - Lorentzon, Mattias; Branco, Jaime; Brandi, Maria Luisa; Bruyère, Olivier; Chapurlat, Roland; Cooper, Cyrus; Cortet, Bernard; Diez-Perez, Adolfo; Ferrari, Serge; Gasparik, Andrea; Herrmann, Markus; Jorgensen, Niklas Rye; et al. (Advances in therapy, 2019)
INTRODUCTION: Increased biochemical bone turnover markers (BTMs) measured in serum are associated with bone loss, increased fracture risk and poor treatment adherence, but their role in clinical practice is presently unclear. The aim of this consensus group report is to provide guidance to clinicians on how to use BTMs in patient evaluation in postmenopausal osteoporosis, in fracture risk prediction and in the monitoring of treatment efficacy and adherence to osteoporosis medication. METHODS: A working group with clinical scientists and osteoporosis specialists was invited by the Scientific Advisory Board of European Society on Clinical and Economic Aspects of Osteoporosis, Osteoarthritis and Musculoskeletal Diseases (ESCEO). RESULTS: Serum bone formation marker PINP and resorption marker βCTX-I are the preferred markers for evaluating bone turnover in the clinical setting due to their specificity to bone, performance in clinical studies, wide use and relatively low analytical variability. BTMs cannot be used to diagnose osteoporosis because of low sensitivity and specificity, but can be of value in patient evaluation where high values may indicate the need to investigate some causes of secondary osteoporosis. Assessing serum levels of βCTX-I and PINP can improve fracture prediction slightly, with a gradient of risk of about 1.2 per SD increase in the bone marker in addition to clinical risk factors and bone mineral density. For an individual patient, BTMs are not useful in projecting bone loss or treatment efficacy, but it is recommended that serum PINP and βCTX-I be used to monitor adherence to oral bisphosphonate treatment. Suppression of the BTMs greater than the least significant change or to levels in the lower half of the reference interval in young and healthy premenopausal women is closely related to treatment adherence. CONCLUSION: In conclusion, the currently available evidence indicates that the principal clinical utility of BTMs is for monitoring oral bisphosphonate therapy.
Keywords: postmenopauzální osteoporóza; inhibitory kostní resorpce; lidé středního věku; Humans; následné studie; Biomarkers; ženské pohlaví; senioři nad 80 let; Middle Aged; Reference Values; Aged, 80 and over; Bone Density; algoritmy; biologické markery; kostní denzita; remodelace kosti; bisfosfonáty; výsledek terapie; Bone Density Conservation Agents; Diphosphonates; Follow-Up Studies; senioři; lidé; Algorithms; Aged; Treatment Outcome; referenční hodnoty; Bone Remodeling; Osteoporosis, Postmenopausal; Female